Microarray expression profiling identifies genes with altered expression in Adolescent Idiopathic Scoliosis - Fendri, Khaled (Springer-Verlag, 2013)
PURPOSE: Adolescent Idiopathic Scoliosis (AIS) is considered a complex genetic disease, in which malfunctioning or dysregulation of one or more genes has been proposed to be responsible for the expressed phenotype. However, to date, no disease causing genes has been identified and the pathogenesis of AIS remains unknown. The aim of this study is, therefore, to identify specific molecules with differing expression patterns in AIS compared to healthy individuals. METHODS: Microarray analysis and quantitative RT-PCR have examined differences in the gene transcription profile between primary osteoblasts derived from spinal vertebrae of AIS patients and those of healthy individuals. RESULTS: There are 145 genes differentially expressed in AIS osteoblasts. A drastic and significant change has been noted particularly in the expression levels of Homeobox genes (HOXB8, HOXB7, HOXA13, HOXA10), ZIC2, FAM101A, COMP and PITX1 in AIS compared to controls. Clustering analysis revealed the interaction of these genes in biological pathways crucial for bone development, in particular in the differentiation of skeletal elements and structural integrity of the vertebrae. CONCLUSIONS: This study reports on the expression of molecules that have not been described previously in AIS. We also provide for the first time gene interaction pathways in AIS pathogenesis. These genes are involved in various bone regulatory and developmental pathways and many of them can be grouped into clusters to participate in a particular biological pathway. Further studies can be built on our findings to further elucidate the association between different biological pathways and the pathogenesis of AIS.